Comparative Analysis of Aqueous Humor Cytokine Levels Between Patients With Exudative Age-Related Macular Degeneration and Normal Controls - Cha, Dong Min; Woo, Se Joon; Kim, Hye-Jung; Lee, Cheolju; Park, Kyu Hyung (ASSOC RESEARCH VISION OPHTHALMOLOGY INC, 2013)
PURPOSE. To investigate the cytokine markers associated with exudative AMD present in aqueous humor. This goal was achieved by comparing the concentrations of more than 500 molecules in aqueous humor, between exudative AMD patients and controls. METHODS. Aqueous humor samples were acquired from 20 patients with exudative AMD and 20 control subjects. Raybio human antibody array technology was used to simultaneously screen for any difference in the expression of any of 507 molecules. To validate the antibody array result, concentrations of insulin-like growth factor binding protein 2 (IGFBP-2), insulin-like growth factor-1 (IGF-1), and VEGF were measured by ELISA. RESULTS. Twenty molecules studied exhibited intergroup differences. Twelve molecules including IGFBP-2, IGFBP-6, IGFBP-7, and glucocorticoid-induced tumor necrosis factor receptor family related gene (GITR) ligand, were detected in high densities in exudative AMD patients. Eight other molecules were present at higher concentrations in control patients. ELISA confirmed that IGFBP-2 levels were higher in patients with exudative AMD (7.47 +/- 6.19 ng/mL) in comparison with control subjects (3.07 +/- 3.34 ng/mL, P = 0.008). IGF-1 and VEGF levels were also increased in the former group (2.20 +/- 0.26 vs. 1.99 +/- 0.35 ng/mL, P = 0.040; 122.25 +/- 63.24 vs. 86.98 +/- 44.41 pg/mL, P = 0.048, respectively). CONCLUSIONS. The pattern of cytokine expression in the aqueous humor of exudative AMD patients varies from that of normal control subjects. The increased levels of IGFBP-2 and IGF-1 in exudative AMD eyes indicate that the altered expression of IGF-related molecules may be involved in disease pathogenesis and suggests potential biomarkers for exudative AMD.
Keywords: ENDOTHELIAL GROWTH-FACTOR; FACTOR-BINDING PROTEIN-2; MONOCYTE CHEMOATTRACTANT PROTEIN-1; POLYPOIDAL CHOROIDAL VASCULOPATHY; EPITHELIUM-DERIVED FACTOR; FACTOR-I; PIGMENT-EPITHELIUM; DIABETIC-RETINOPATHY; IGF-II; CELLS